Delays and Factors Related to Cessation of Generalized Convulsive Status Epilepticus. - Kämppi L; Ritvanen J; Mustonen H; Soinila S (United States, 2022)
Introduction. This study was designed to identify the delays and factors related to and predicting the cessation of generalized convulsive SE (GCSE). Methods. This retrospective study includes 70 consecutive patients (>16 years) diagnosed with GCSE and treated in the emergency department of a tertiary hospital over 2 years. We defined cessation of SE stepwise using clinical seizure freedom, achievement of burst-suppression, and return of consciousness as endpoints and calculated delays for these cessation markers. In addition 10 treatment delay parameters and 7 prognostic and GCSE episode related factors were defined. Multiple statistical analyses were performed on their relation to cessation markers. Results. Onset-to-second-stage-medication (p = 0.027), onset-to-burst-suppression (p = 0.005), and onset-to-clinical-seizure-freedom (p = 0.035) delays correlated with the onset-to-consciousness delay. We detected no correlation between age, epilepsy, STESS, prestatus period, type of SE onset, effect of the first medication, and cessation of SE. Conclusion. Our study demonstrates that rapid administration of second-stage medication and early obtainment of clinical seizure freedom and burst-suppression predict early return of consciousness, an unambiguous marker for the end of SE. We propose that delays in treatment chain may be more significant determinants of SE cessation than the previously established outcome predictors. Thus, streamlining the treatment chain is advocated.